Cardiac magnetic resonance defines mechanisms of sex-based differences in outcomes following cardiac resynchronization therapy - Bivona, Derek J.; Tallavajhala, Srikar; Abdi, Mohamad; Oomen, Pim J. A.; Gao, Xu; Malhotra, Rohit; Darby, Andrew; Monfredi, Oliver J.; Mangrum, J. Michael; Mason, Pamela; Mazimba, Sula; Salerno, Michael; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Mechanisms of sex-based differences in outcomes following cardiac resynchronization therapy (CRT) are poorly understood. Objective: To use cardiac magnetic resonance (CMR) to define mechanisms of sex-based differences in outcomes after CRT and describe distinct CMR-based phenotypes of CRT candidates based on sex and nonischemic/ischemic cardiomyopathy type. Methods: Sex-based differences in three short-term CRT response measures (fractional change in left ventricular end-systolic volume index 6 months after CRT [LVESVI-FC], B-type natriuretic peptide [BNP] 6 months after CRT, change in peak VO2 6 months after CRT), and long-term survival were evaluated with respect to 39 baseline parameters from CMR, exercise testing, laboratory testing, electrocardiograms, comorbid conditions, and other sources. CMR was assessed using the CURE-SVD parameter determined with displacement encoding with stimulated echoes (DENSE) strain imaging. Statistical methods included multivariable linear regression with evaluation of interaction effects associated with sex and cardiomyopathy type (ischemic and nonischemic cardiomyopathy) and survival analysis. Results: Among 200 patients, the 54 female patients (27%) pre-CRT had smaller CMR-based LVEDVI (p = 0.04), more mechanical dyssynchrony based on the validated CMR CURE-SVD parameter (p = 0.04), a lower frequency of both late gadolinium enhancement (LGE) and ischemic cardiomypathy (p < 0.0001), a greater RVEF (p = 0.02), and a greater frequency of LBBB (p = 0.01). After categorization of patients into four groups based on cardiomyopathy type (ischemic/nonischemic cardiomyopathy) and sex, female patients with nonischemic cardiomyopathy had the lowest CURE-SVD (p = 0.003), the lowest pre-CRT BNP levels (p = 0.01), the lowest post-CRT BNP levels (p = 0.05), and the most favorable LVESVI-FC (p = 0.001). Overall, female patients had better 3-year survival before adjustment for cardiomyopathy type (p = 0.007, HR = 0.45) and after adjustment for cardiomyopathy type (p = 0.009, HR = 0.67). Conclusion: CMR identifies distinct phenotypes of female CRT patients with nonischemic and ischemic cardiomyopathy relative to male patients stratified by cardiomyopathy type. The more favorable short-term response and long-term survival outcomes in female heart failure patients with CRT were associated with lower indexed CMR-based LV volumes, decreased scar burden on LGE, and greater CMR-based dyssynchrony with the CURE-SVD.